Kontribusi Kepercayaan Diri Terhadap Kemampuan Penalaran Matematis Siswa SMA di Kota Surakarta - Muhamad Akrom (Lembaga Bale Literasi, 2021)
This study aims to determine the contribution of self-confidence to the mathematical reasoning abilities of high school students. The method used in this research is a survey method with correlation and regression techniques. The research sample was 93 high school students in the city of Surakarta, Central Java, Indonesia, with different abilities. The instrument used in this study was a written test of mathematical reasoning abilities on absolute value material, as well as a set of self-confidence questionnaire statements. Data analysis of mathematical reasoning ability and self-confidence in this study is the Pearson correlation analysis and regression with the help of SPSS 16.0. The results of the research data analysis showed that there was a positive correlation between self-confidence and students' mathematical reasoning abilities. The contribution of self-confidence to mathematical reasoning ability was 13.1% in the medium category. Students who have good self-confidence will always think positively that they are confident in their abilities, can solve special problems that require reasoning, thereby significantly increasing their reasoning abilities.